2017
DOI: 10.1016/s2214-109x(17)30331-5
|View full text |Cite
|
Sign up to set email alerts
|

How Ethiopia achieved Millennium Development Goal 4 through multisectoral interventions: a Countdown to 2015 case study

Abstract: SummaryBackground3 years before the 2015 deadline, Ethiopia achieved Millennium Development Goal 4. The under-5 mortality decreased 69%, from 205 deaths per 1000 livebirths in 1990 to 64 deaths per 1000 livebirths in 2013. To understand the underlying factors that contributed to the success in achieving MDG4, Ethiopia was selected as a Countdown to 2015 case study.MethodsWe used a set of complementary methods to analyse progress in child health in Ethiopia between 1990 and 2014. We used Demographic Health Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
143
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(151 citation statements)
references
References 33 publications
6
143
1
1
Order By: Relevance
“…The percentage of households with low unimproved water coverage were linked with the latter two quintiles. The spatial distribution of unimproved water sources observed among regions and wealth quintiles were similar with previous studies [17,30,31]. It also corroborates studies which indicated variations in access to improved water attributed by wealth status [15,16].…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of households with low unimproved water coverage were linked with the latter two quintiles. The spatial distribution of unimproved water sources observed among regions and wealth quintiles were similar with previous studies [17,30,31]. It also corroborates studies which indicated variations in access to improved water attributed by wealth status [15,16].…”
Section: Discussionsupporting
confidence: 90%
“…Maternal, newborn, and child health have a high stake in the global health agenda including Ethiopia; however, millions of newborn babies are dying as a result of easily preventable causes [12][13][14]. Infectious diseases (sepsis, meningitis, and pneumonia), preterm birth complications, and intrapartum complications (including asphyxia) are the leading causes of death in the world [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Even in Sub‐Saharan Africa, the region with the highest under‐five mortality rate, there was a substantial reduction . Ethiopia met the Millennium Development Goal 4 by reducing the under‐five mortality from 205 deaths per 1000 live births in 1990 to 64 deaths per 1000 live births in 2013 .…”
Section: Introductionmentioning
confidence: 99%
“…The success of reducing the under‐five mortality by two‐thirds over the past 20 years could be attributed to improvements in multiple sectors including increased access to lifesaving health system interventions . These interventions include improved availability of outpatient care for sick children, expanded coverage of immunisations and an increased number of facilities that provide treatment, growth monitoring and nutrition services .…”
Section: Introductionmentioning
confidence: 99%